Increased separase activity and occurrence of centrosome aberrations concur with transformation of MDS - Ruppenthal, Sabrina; Kleiner, Helga; Nolte, Florian; Fabarius, Alice; Hofmann, Wolf-Karsten; Nowak, Daniel; Seifarth, Wolfgang (PLOS ONE, 2018)
ESPL1/separase, a cysteine endopeptidase, is a key player in centrosome duplication and mitotic sister chromatid separation. Aberrant expression and/or altered separase proteolytic activity are associated with centrosome amplification, aneuploidy, tumorigenesis and disease progression. Since centrosome alterations are a common and early detectable feature in patients with myelodysplastic syndrome (MDS) and cytogenetic aberrations play an important role in disease risk stratification, we examined separase activity on single cell level in 67 bone marrow samples obtained from patients with MDS, secondary acute myeloid leukemia (sAML), de novo acute myeloid leukemia (AML) and healthy controls by a flow cytometric separase activity assay. The separase activity distribution (SAD) value, a calculated measure for the occurrence of cells with prominent separase activity within the analyzed sample, was tested for correlation with the centrosome, karyotype and gene mutation status. We found higher SAD values in bone marrow cells of sAML patients than in corresponding cells of MDS patients. This concurred with an increased incidence of aberrant centrosome phenotypes in sAML vs. MDS samples. No correlation was found between SAD values and the karyotype/gene mutation status. During follow-up of four MDS patients we observed increasing SAD values after transformation to sAML, in two patients SAD values decreased during azacitidine therapy. Cell culture experiments employing MDS-L cells as an in vitro model of MDS revealed that treatment with rigosertib, a PLK1 inhibitor and therapeutic drug known to induce G2/M arrest, results in decreased SAD values. In conclusion, the appearance of cells with unusual high separase activity levels, as indicated by increased SAD values, concurs with the transformation of MDS to sAML and may reflect separase dysregulation potentially contributing to clonal evolution during MDS progression. Separase activity measurement may therefore be useful as a novel additional molecular marker for disease monitoring.